Analisis kondisi sosio demografi, ekonomi, dan ekologi wilayah di kawasan eks transmigrasi perkebunan kelapa sawit Kecamatan Muara Papalik Kabupaten Tanjung Jabung Barat - Prasetio, Heru; Suandi, Suandi; Junaidi, Junaidi (Jurnal Paradigma Ekonomika, 2022)
The unit of analysis in this study is at the household level. Sources of data come from primary data and secondary data. The data collection method is a survey method using a questionnaire. Samples of data were taken from as much as 10% of the total population in the research location. Data were analyzed descriptively. The research focused on ex-transmigration areas' socio-demographic, economic, and ecological conditions in oil palm plantation communities. Based on the study results, it can be seen that the socio-demographic needs of the ex-transmigration community in Muara Papalik District are feasible and sufficient. The economic condition of the ex-transmigration community in Muara Papalik District in general, the welfare level of ex-transmigrants in Muara Papalik District can be said to be high. Judging from the ecological conditions of the region, the ex-transmigration area in Muara Papalik District has the potential to be developed sustainably. Proper and sufficient demographic conditions support the environmental growth of the region. In addition, the economic situation of the ex-transmigration community also has a significant influence on the development of the Muara Papalik sub-district.